The alkaline transition of cytochrome c revisited: Effects of electrostatic interactions and tyrosine nitration on the reaction dynamics - Oviedo Rouco, Santiago (2019)
Here we investigated the effect of electrostatic interactions and of protein tyrosine nitration of mammalian cytochrome c on the dynamics of the so-called alkaline transition, a pH- and redox-triggered conformational change that implies replacement of the axial ligand Met80 by a Lys residue. Using a combination of electrochemical, time-resolved SERR spectroelectrochemical experiments and molecular dynamics simulations we showed that in all cases the reaction can be described in terms of a two steps minimal reaction mechanism consisting of deprotonation of a triggering group followed by ligand exchange. The pK a alk values of the transition are strongly modulated by these perturbations, with a drastic downshift upon nitration and an important upshift upon establishing electrostatic interactions with a negatively charged model surface. The value of pK a alk is determined by the interplay between the acidity of a triggering group and the kinetic constants for the forward and backward ligand exchange processes. Nitration of Tyr74 results in a change of the triggering group from Lys73 in WT Cyt to Tyr74 in the nitrated protein, which dominates the pK a alk downshift towards physiological values. Electrostatic interactions, on the other hand, result in strong acceleration of the backward ligand exchange reaction, which dominates the pK a alk upshift. The different physicochemical conditions found here to influence pK a alk are expected to vary depending on cellular conditions and subcellular localization of the protein, thus determining the existence of alternative conformations of Cyt in vivo.